1982
DOI: 10.1007/bf00017129
|View full text |Cite
|
Sign up to set email alerts
|

On the energy release rate and the J-integral for 3-D crack configurations

Abstract: In this paper an analytical expression for the energy release rate has been derived and put in a form suitable for a numerical analysis of an arbitrary 3-D crack configuration. The virtual crack extension method can most conveniently be used for such a derivation. This method was originally developed from finite element considerations and the resulting expressions were, therefore, based on the finite element matrix formulation [1][2][3][4][5]. In this paper the derivation of the energy release rate leads to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
94
0
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(96 citation statements)
references
References 7 publications
0
94
0
2
Order By: Relevance
“…(2) is cumbersome in the FE scheme as the contour is preferably selected to pass through Gauss points where stresses are expected to be the most accurate. To circumvent this difficulty, the line-integral form of J can be recast as a domain integral (DeLorenzi, 1982;Li et al, 1985). Let us assume q is a sufficiently smooth scalar function in the region enclosed by Γ c = Γ 0 + Γ + + Γ − − Γ, holding unity on Γ and vanishing on Γ 0 .…”
Section: J-integralmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) is cumbersome in the FE scheme as the contour is preferably selected to pass through Gauss points where stresses are expected to be the most accurate. To circumvent this difficulty, the line-integral form of J can be recast as a domain integral (DeLorenzi, 1982;Li et al, 1985). Let us assume q is a sufficiently smooth scalar function in the region enclosed by Γ c = Γ 0 + Γ + + Γ − − Γ, holding unity on Γ and vanishing on Γ 0 .…”
Section: J-integralmentioning
confidence: 99%
“…It has been shown that the domain version of the J-integral has superior path independence than does the line integral, yielding much more accurate results for the crack field parameters (Nikishkov and Atluri, 1987a;Raju and Shivakumar, 1990). The domain integral method corresponds to a continuum formulation of the finite-element virtual crack extension technique (DeLorenzi, 1982). One can refer to Moran and Shih (1987a,b) for a general discussion on crack-tip contour integrals and their associated domain integral representation.…”
Section: J-integralmentioning
confidence: 99%
See 1 more Smart Citation
“…For evaluating the SIF, the analysis is carried out for the applied displacement of 0.01 mm in each specimen and the corresponding compliance values are calculated for each value of a/W. Many approaches exist in the literature (Paris and Sih 1965;Ingraffea and Manu 1980;Raju and Newman 1977;De Lorenzi 1982;Parks 1974) to determine the SIF values. If all approaches are broadly categorized, there are two different methods with which SIF can be derived from the compliance data.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…The extrapolation techniques are based on asymptotic displacement and stress fields near the crack-front (Paris and Sih 1965): by the displacement-field approach (Ingraffea and Manu 1980) and by nodal-force approach (Raju and Newman 1977). The indirect method on the other hand is one where K is determined via its relation with other quantities such as the compliance, the elastic energy (G), or the J integral (De Lorenzi 1982;Parks 1974). For indirect methods, it is possible to calculate the compliance for a range of different crack sizes; from the data using numerical differentiation with respect to crack size SIF can be evaluated.…”
Section: Analytical Frameworkmentioning
confidence: 99%